UNSUR MORFEMIS UNIK PENDUKUNG SITUASI ARKAIS PADA JANTURAN (THE UNIQUE OF MORPHEME ELEMENTS THAT SUPPORT THE ARCHAIC SITUATION ON JANTURAN) - NFN Mulyanto (Kadera Bahasa, 2016)
There are some bound morphemes in Java language that are only used as a form of archaic with a certain uniqueness. These morphemes are believed to have a feel of beauty in certain aspects. They are used mainly in ceremonies or performing arts. The language elements are also used by the puppeteer in a puppet performance. In general, the inclusion of these elements are difficult tounderstand by Javanese speakers nowadays. Some morphemes are important to be described so that they will be easily understood by all the speakers of the Java language. The data were obtained from the language used by the puppeteer in the scenes jejer called Janturan. The model of analysis used substitute technique in order to see whether the using of the morpheme have added the archaic nuance to the related words. The result showed that the supporting morphemes of the archaic aspect are {-in}, {ka-}, {-um-}, {(h)aN-}, {(h)a-}, {-ing}, {den-}, variation /a/ on /e/, and the dwipurwa repetition.